Determination of minor quantities of linezolid polymorphs in a drug substance and tablet formulation by powder X-ray diffraction technique. Issue 2 (2nd March 2017) - Sun, Mengying; Hu, Xiurong; Zhou, Xinbo; Gu, Jianming
Abstract : Linezolid (LZD) is one of the first commercially available synthetic oxazolidinone antibiotics and is widely used for the treatment of multidrug-resistant Gram-positive bacterial infection. LZD was found to have five polymorphic forms. The most stable and commercialized polymorphs are known as forms II and IV. Trace content of form II in LZD form IV will cause to transition LZD form IV to II rapidly. Powder X-ray diffraction (PXRD) methods were evaluated for the determination of the polymorphic content of the drug substance and drug product. The estimated limit of detection values of the single peak method for LZD polymorph form II in drug substance and tablet formulation were 0.4 and 0.6%, respectively, while the limit of detection value of Rietveld Refinement (full-profile fitting) evaluated LZD polymorph form II in drug substance was 0.2%. The results clearly show that levels <1 wt.% (in active pharmaceutical ingredients) and 2 wt.% (in tablets) LZD form II in form IV can be detected and quantified by PXRD. Validation of the analytical method proved that the method is repeatable, sensitive, and accurate.